Symmetry problem 1 - Ramm, Alexander G. (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
A symmetry problem is solved. A new method is used. The idea of this methodis to reduce to a contradiction the PDE and the over-determined boundary data on the boundary.The new method allows one to solve other symmetry problems.